2012
DOI: 10.1002/jccs.201100481
|View full text |Cite
|
Sign up to set email alerts
|

The First Synthesis of Natural Occurring Juncaceae Coumarin, 9‐Hydroxy‐8‐methyl‐3H‐benzo[f]chromen‐3‐one, Featuring a One‐pot Rearrangement and Aromatization Cascade

Abstract: The synthesis of benzocoumarins from b-tetralones has been achieved via two pathways in the first total synthesis of the Juncaceae natural product, 9-hydroxy-8-methyl-3H-benzo[f]chromen-3-one, featuring a one-pot rearrangement and aromatization cascade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…From the Juncus acutus plant's rhizomes, Della-Greca and colleagues extracted several bioactive benzocoumarins which symbolized as BC 31-BC37 [31]. Then, starting with β-tetralone and through two different pathways including a onepot aromatization and rearrangement chain reactions, Hon's research team reported the total synthesis of the BC33 for the first time [74].…”
Section: Juncus Benzocoumarin Total Synthesismentioning
confidence: 99%
“…From the Juncus acutus plant's rhizomes, Della-Greca and colleagues extracted several bioactive benzocoumarins which symbolized as BC 31-BC37 [31]. Then, starting with β-tetralone and through two different pathways including a onepot aromatization and rearrangement chain reactions, Hon's research team reported the total synthesis of the BC33 for the first time [74].…”
Section: Juncus Benzocoumarin Total Synthesismentioning
confidence: 99%
“…[4][5] Recent years have witnessed increasing interest in π-expanded coumarins, as they display a wide spectrum of biological activities (Figure 1). [6] Therefore, the ability to quickly assemble a πexpanded coumarin from a readily available starting material is highly significant. [7] 5,6-Benzocoumarin is an important π-expanded coumarin motif, with various routes for its synthesis having been reported (Scheme 1).…”
mentioning
confidence: 99%
“…Examples of synthetic biologically active π-expanded coumarins. [6] Scheme 1. Synthetic routes to 5,6-benzocoumarins.…”
mentioning
confidence: 99%